Statistical evaluation of the stock market’s role in contemporary terms of Ukrainian economy’s development - Evseenko O. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper assessed the influence of the main factors that characterize the state of the modern stock market in Ukraine on the socio-economic development of the country.